Política Externa Brasileira para mudanças climáticas: Conferências das Partes da Convenção-Quadro de Copenhagen e Paris - Dias, Denise Kobayashi (2019)
Climate change is a phenomenon that affects all states on our planet and fundamentally transcends borders. Thus, the responsibility of states to shape international cooperation materialized in the United Nations Framework Convention on Climate Change (UNFCCC) in 1992, so that the formalization of the international environmental regime was reaffirmed from the Kyoto Protocol in 1997, which seeks to reduce greenhouse gas emissions. This master’s thesis aims to analyze the Brazilian position at the Conference of the Parties of Copenhagen and Paris, 2009 and 2015, respectively. The methodology was based on analysis of official documents such as COP reports; official speeches; secondary sources such as articles related to the theme and journalistic reports about the period analyzed. Brazil starts from the assumption of the principles of common but differentiated responsibilities and throughout the regime presents progressive inflections to help establish a binding international agreement.